Huma Betang dan Keterbatasan Semiotika Struktural: Negosiasi Makna Budaya dalam Komunikasi Dayak Era Pasca-Reformasi - Rico Rico; Andi Faisal Bakti; Frengki Napitupulu; Risa Dwi Ayuni (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2026)
The Huma Betang symbol among the Dayak community in Central Kalimantan has undergone a significant shift in meaning during the Post-Reform era, driven by modernization, cultural globalization, and the rapid growth of digital media. This study critically examines the limitations of Ferdinand de Saussure's structural semiotics in accounting for the evolving dynamics of meaning negotiation within contemporary cultural realities. The research employs an interpretive paradigm with a qualitative design, drawing on in-depth interviews, observation, and documentation involving traditional leaders, cultural practitioners, and members of the Dayak community. The analysis is grounded in Saussurean semiotics and cultural communication perspectives. Findings reveal that the meaning of Huma Betang is not static; rather, it is continuously negotiated through social interaction, generational change, and digital communication. Saussurean semiotics proves limited in addressing the fluid, contextual, and ideologically laden nature of cultural meaning. This study proposes Dynamic Structuralism — a semiotic extension that incorporates contextual, temporal, discursive, and interpretive dimensions of cultural meaning — thereby offering a more adaptive reading of cultural communication in understanding local symbols amid social transformation.